Diskriminasi Terhadap Penderita Orang Dengan HIV/AIDS Di Kabupaten Asahan Sumatera Utara - Saputri, Maya; Yunus, Saifuddin; Fakhrurrazi, Fakhrurrazi; Maliati, Nulwita (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2024)
This study examines discrimination against PLHA sufferers (people with HIV/AIDS) (Case Study in Air Joman District, Asahan Regency, North Sumatra). The main question of this research is what is society's knowledge about HIV/AIDS, because discrimination is related to society's knowledge. Other questions studied are the reasons why society discriminates against HIV/AIDS sufferers and strategies to prevent discrimination against PLWHA in Air Joman District. The theoretical perspective used in this study is labeling theory. This perspective states that discrimination occurs because of society's negative prejudice towards HIV/AIDS sufferers. The data collection method was carried out qualitatively, namely through observation and in-depth interviews and also document study. The findings of this dissertation show that the knowledge of the people in Air Joman District about HIV/AIDS is (a) HIV/AIDS is a disease caused by deviant behavior; (b) HIV/AIDS is an infectious disease and can be transmitted to other people. The reasons why society discriminates against HIV/AIDS sufferers in Air Joman District are (a) Not wanting to be infected with HIV/AIDS, and (b) Dislike of HIV/AIDS sufferers. The strategy to prevent discrimination against PLWHA in Air Joman District is (a) the strategy of health workers, including conducting HIV/AIDS outreach to the community and youth through the dissemination of material about HIV/AIDS and distribution of HIV/AIDS brochures; (b) the strategy of religious leaders, namely the ustaz gives religious lectures about the sin of discriminating against sick people because it can break friendships, wisdom from illness and mercy for people who care about sick people, and avoiding immoral acts that trigger HIV/AIDS such as free sex which is prohibited in Islamic Religion.